(untitled) (Academia Science Repository, 2023)
The article discusses the directions of investment activity in the context of the globalization of the economy, as well as the features of the development of the state in the context of globalization, identified problems, made proposals for the development of foreign economic relations in order to deepen globalization, financing investment capital contributing to the development of the economy of Uzbekistan. The directions of the country’s globalization are reflected, as well as proposals are evaluated and proposed.